PERLINDUNGAN HUKUM BAGI KREDITUR DALAM HAL BENDA JAMINAN BERALIH - Purna Mahendra, Andre; Sekar, I Dewa Nyoman (Kertha Semaya : Journal Ilmu Hukum, 2013)
Stipulation of Article 23 paragraph (2) and Article 3 of law concerning legalprotection for creditor in case altering the fiduciary shall be registration or theobligation of the debtor to provide alternative substituting assurance which shares theequal value. Upon normative legal research analysis, it shall be concluded that theaction committed by the debtor in altering the fiduciary warrant object without anyconsent by the recipient of fiduciary shall be a breach of law, as it is prohibited by law.Hence, this writing shall explain the legal protection for creditor in case altering thefiduciary warrant object.
Keywords: Fiduciary, Substituting Assurance, Debtor, Legal Protection